FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA INTIAL PUBLIC OFFERING (IPO) DI BEI PERIODE TAHUN 2013-2017 - suwandi suwandi (Universitas Malahayati, 2018)
The purpose of this study was to determine the effect offirm size, firm age, the percentage of sharesoffered, underwriter reputation, financial leverage, and ROE (Return On Equity) to the underpricingof stock in an Initial Public Offering (IPO). The data usedare secondary data that did IPOcompanieslisted on the Indonesian Stock Exchange (BEI) in 2013-2017. Analysis data technique usedmultiple linear regression.The results showed that the ROE has a significant effect on underpricingand variables of firm size, firm age, the percentage of shares offered, underwriter reputation, financialleverage in significant effected on underpricing.The results of simultaneously F test showed that therewas a significant difference between firm size, firm age, the percentage ofshares offered, underwriterreputation, financial leverage, and ROE on underpricing of IPO shares.